Дослідження поселення козацької доби біля с. Медведівка - Пашковський, О.А. (Археологічні дослідження в Україні, 2010)
In 2009, a small-scale research in Medvedivka village, a former Sotnyk’s town, in Chyhyryn Region of Cherkasy Oblast was conducted.